ANALISIS LAJU KOROSI BESI BETON DENGAN MEDIUM TANAH RAWA - Rahmaniah, Rahmaniah; Amalia, Nurul; Ihsan, Ihsan (JFT : Jurnal Fisika dan Terapannya, 2019)
The research on corrosion rate analysis of concrete iron with swampsoil medium has been conducted. The aims of this study were to determine thecorrosion rate and the types of corrosion that occurred in concrete iron withswamp soil medium. The methods of this study are Weight Loss method, AtomicAbsorption Spectroscopy (AAS) test, and Scanning Electron Microscope-EnergyDispersion X-Ray (SEM-EDX). This study used a different immersion timevariant, such as 20 days, 40 days, 65 days, and without medium for 65 days. Theconcrete iron used in this study is concrete U-24 or plain concrete iron 10. Thecorrosion rate that occurs in iron concrete with swamp soil medium at 20 daysimmersion is 20977.5868 mmpy, 40 days immersion is 17721.9174 mmpy, 65days immersion is 16932. 9071 and 65 days without a medium are 3023.3793mmpy. The more time, the rate of corrosion become more slowly due to theinfluence of corrosion products that have occurred. The corrosion rate without themedium is slower than the corrosion rate with the medium. The types of corrosionthat occurs in concrete iron with swamp soil medium are crevice corrosion andpitting corrosion.